HLA-DR products are a subset of human Ia antigens. - Makgoba, M; Fuggle, S; Mcmichael, A; Morris, P (1983)
Human Ia antigens are polymorphic cell-surface sialoglycoproteins which have restricted tissue distribution. They are bimolecular complexes of 34,000 (alpha) and 28,000 (beta) molecular weight and most of the polymorphism is found in the smaller polypeptides. They are involved in the initiation of immune responses and particular Ia antigens are associated with increased susceptibility to certain diseases. They are also the major barrier to human allogeneic tissue transplantation. Whereas serological analysis and mixed lymphocyte typing have defined three polymorphic families of Ia antigens, HLA-DR, -DC and -SB, protein sequencing results and studies with monoclonal antibodies indicate that the complexity is much greater. Thus the HLA-DR and DC specificities as defined by alloantisera, could represent groups of antigens which are controlled by HLA genes in linkage disequilibrium. Here, we have used a monoclonal antibody specific for HLA-DR2 to show that this determinant is carried by molecules which are distinct from those of the DC series and which represent 30% of the Ia antigens expressed on the cell surface of an HLA homozygous line PGF.